Artificial intelligence as a paradigm in university education: challenges and solutions - Lubko, Dmytro; Лубко, Дмитро Вікторович (My University, 2024)
EN: The article examines the problem of teaching artificial intelligence in universities, the difficulties of this process and ways to solve them. It is noted that the teaching of artificial intelligence in universities faces a number of problems. There is a shortage of qualified teachers in the field of artificial intelligence. The rapid pace of development of this field requires constant updating of educational programs and materials. The topic itself is quite technical and requires students to have a deep understanding of mathematical models, algorithms and programming. The difficulty of studying artificial intelligence at a university is the need for a wide range of knowledge and skills. Lack of practical experience of teachers and students of higher education, etc. Ways to solve the highlighted problems are proposed. /// UA: У статті розглядається проблема навчання штучного інтелекту в університетах, труднощі цього процесу та шляхи їх вирішення. Зазначається, що викладання штучного інтелекту в університетах стикається з низкою проблем. Не вистачає кваліфікованих викладачів у сфері штучного інтелекту. Швидкі темпи розвитку цієї галузі потребують постійного оновлення навчальних програм і матеріалів. Сама тема досить технічна і вимагає від студентів глибокого розуміння математичних моделей, алгоритмів і програмування. Складність вивчення штучного інтелекту в університеті полягає в необхідності широкого спектру знань і навичок. Відсутність практичного досвіду викладачів і здобувачів вищої освіти тощо. Пропонуються шляхи вирішення висвітлених проблем.
Keywords: university; education; artificial intelligence training; students; knowledge; університет; освіта; навчання штучному інтелекту; здобувачі вищої освіти; знання